2015
DOI: 10.3892/ol.2015.3766
|View full text |Cite
|
Sign up to set email alerts
|

Transient pancytopenia preceding adult acute lymphoblastic leukemia with chromosomal abnormalities including the Philadelphia chromosome: A case report and review of the literature

Abstract: Abstract.A preleukaemic phase, typified by transient pancytopenia, is a rare occurrence that usually affects children and adolescents. The present study reports the case of a 50-yearold woman with transient pancytopenia, which manifested as a fever, cough and severe anemia. Three weeks following treatment of pancytopenia with antibiotics, red blood cell and platelet transfusion, granulocyte colony-stimulating factor and human γ globulin, the condition of the patient was improved. However, 3 weeks following dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Even though it is a well-documented consensus that myelodysplastic syndrome can precede acute non-lymphoblastic leukemia, pre-ALL it is still an unclear, rare entity with a prevalence of 1.3-2.2% in children diagnosed with ALL (8,16,17). The initial symptom of pre-ALL is fever associated to pancytopenia revealed by the CBC count, and it usually occurs in children under the age of 10, affecting predominantly girls (18). On one hand, similarly to the previous mentioned data from the literature, the age of our patient was 2 years, but on the other hand he was a boy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even though it is a well-documented consensus that myelodysplastic syndrome can precede acute non-lymphoblastic leukemia, pre-ALL it is still an unclear, rare entity with a prevalence of 1.3-2.2% in children diagnosed with ALL (8,16,17). The initial symptom of pre-ALL is fever associated to pancytopenia revealed by the CBC count, and it usually occurs in children under the age of 10, affecting predominantly girls (18). On one hand, similarly to the previous mentioned data from the literature, the age of our patient was 2 years, but on the other hand he was a boy.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is clear that pre-ALL is a very rare condition that occurs in children and adolescents. Nevertheless, Liang et al reported a case of 50-year-old female with transient pancytopenia presenting with fever, cough and anemia, who was diagnosed with ALL 3 weeks after the treatment for pancytopenia (18). Similarly, our patient was diagnosed with ALL after approximately 2 weeks from the moment of discharge.…”
Section: Discussionmentioning
confidence: 48%
“…Также периоды длительной аплазии костного мозга могут приводить к снижению терапевтической эффективности терапии острых лейкозов и апластической анемии [37]. Изучается непосредственная роль парвовируса B19 в патогенезе острого лимфобластного лейкоза [38,39].…”
Section: л е к ц и яunclassified